Influence of roller burnishing contact width and burnishing orientation on surface quality and tribological behaviour of Aluminium 6061 - ELTAYEB, N; LOW, K; BREVERN, P (Engineering, 2007)
Burnishing is a cold working, surface treatment process in which plastic deformation of surface irregularities occurs by exerting pressure through a very hard and smooth roller or ball on a surface to generate a uniform and work-hardened surface. In this study, a simple burnishing tool, with interchangeable adapter for ball and roller were designed and fabricated to perform roller burnishing processes on Aluminium 6061 under different parameters and different burnishing orientations. The impact of burnishing speed, burnishing force and burnishing tool dimension on the surface qualities and tribological properties were investigated. It was found that burnishing speed of 330 rpm and burnishing force of 212N is capable of improving surface roughness as much as 40%. However, an increase in the roller contact width leads to less improvement in the surface roughness. Meanwhile, roller burnishing also enhance the hardness of burnished Aluminium 6061 by 20-30%.